2022
DOI: 10.2147/idr.s348700
|View full text |Cite
|
Sign up to set email alerts
|

How Good are Bacteriophages as an Alternative Therapy to Mitigate Biofilms of Nosocomial Infections

Abstract: Bacteria survive on any surface through the generation of biofilms that provide a protective environment to grow as well as making them drug resistant. Extracellular polymeric matrix is a crucial component in biofilm formation. The presence of biofilms consisting of common opportunistic and nosocomial, drug-resistant pathogens has been reported on medical devices like catheters and prosthetics, leading to many complications. Several approaches are under investigation to combat drug-resistant bacteria. Deployme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 237 publications
(243 reference statements)
0
10
0
Order By: Relevance
“…The age of the biofilm could have impacted the treatment process. In younger biofilms, exopolymeric components are more easily degraded by phages due to the high bacterial cell density and the rapid phage dispersion in the biofilm structure [50]; however, older biofilms prevent the phage from entering the core layers due to the formed thick matrix [51].…”
Section: Discussionmentioning
confidence: 99%
“…The age of the biofilm could have impacted the treatment process. In younger biofilms, exopolymeric components are more easily degraded by phages due to the high bacterial cell density and the rapid phage dispersion in the biofilm structure [50]; however, older biofilms prevent the phage from entering the core layers due to the formed thick matrix [51].…”
Section: Discussionmentioning
confidence: 99%
“…Bacteriophages are an effective tool against biofilms formed by nosocomial, which are often multi-drug-resistant, strains of bacteria [ 20 , 21 ]. This has been proven by numerous studies by various research groups [ 8 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was also observed by other research groups. Singh et al [ 21 ] and Ammons et al [ 37 ] have reported that the addition of lactoferrin to the medium prevented Pseudomonas aeruginosa from forming biofilms. Additionally, Quinteiri et al [ 17 ] have observed that application of 2.5 mg/mL lactoferrin hydrolysate solution on biofilms attached to glass surfaces caused biofilm dispersion.…”
Section: Discussionmentioning
confidence: 99%
“…This section aims to contextualize the reader providing a concise description of the primary approaches currently employed or under investigation for treating established biofilms, categorized according to their mechanisms of action, and Figure 2 illustrates them. Detailed description can be found in Asma et al, 2022 and Singh, Padmesh, et al, 2022 (Asma et al, 2022; Singh, Amod, et al, 2022). In addition, a list with some examples and references including more detailed information about specific biofilm treatment strategies is presented in Table 1.…”
Section: Biofilms and Antibiofilm Therapiesmentioning
confidence: 99%